The Effect of Listen and do Activity on Students Listening Ability at The Eighth Grade of SMP Negeri 5 Idanogawo in 2022/2023 - Meiman Edi Putra Hura; Triman Harefa; Afore Tahir Harefa; Yaredi Waruwu (Journal on Education, 2023)
Listening is an important skill that should be mastered by the students in the classrooms since the skill involves a process of understanding spoken message. The syllabus of Junior High School expects the students to have a good ability to understand the meaning they listen from the monologue text but reality shows the reverse. The Eight Grade of SMP Negeri 5 Idanogawo are not able to fulfill the expectation in the syllabus. After finding out the problem, the researcher want to find the effect of Listen on the students’ ability in listening skill. This research will be conducted through a quasi-experimental design. The population of this study was class VIII students of SMP Negeri 5 Idanogawo for the 2022/2023 academic year, totaling 60 students of class VIII A- of SMP Negeri 5 idanogawo as the informant. the research chooses class VIII B - as the sample of the research because based on the information from the english teacher that the class was in middle score lowest. After validating the test, the researcher will give the pre-test to both classes to examine the normality of the data and homogeneity of the sample. Moreover, after giving treatment, the researcher administers the post test in both of the classes to get the result of the treatment and to examine the result of the normality of the data and homogeneity. Furthermore, the purpose of the research is to find whether there is a significant Effect of Listen and Do Activity on Students Listening Ability at the eight Grade of SMP Negeri 5 Idanogawo in 2022/2023.